Exposed! The Public Life of Carboniferous Fossils in the Burren and Cliffs of Moher UNESCO Global Geopark, Ireland - Eamon Doyle (Geoconservation Research)
Carboniferous fossils from the Burren and Cliffs of Moher UNESCO Global Geopark, County Clare, Ireland are rated by their promotional potential in the form of celebrity A, B or C-listings. Trace fossils, crinoids, brachiopods, corals and vertebrates are the most exposed to public view at a number of high-profile visitor locations and the relative risk to the fossils to increased public exposure is assessed. The least abundant fossils, the vertebrates, have the highest promotional potential, while locally well-known trace fossils are also considered high potential. The invertebrates are of lower promotional value; however, that is changing with increasing public education. Currently, fossils get limited exposure on Geopark websites and social media platforms. The use of fossils to provide content to social media and other geotourism promotional material should be encouraged but requires a balance between the needs of geoconservation, scientific study and geotourism exploitation that requires selective use of fossils and careful promotional writing.